A COMPARATIVE STUDY OF DIFFERENT METHODS FOR OBTAINING AN INDEX OF NITROGEN AVAILABILITY IN UPLAND SOILS - HUSSAIN , FAOIR; MALIK , KAUSER A.; NAQVl , MAZIlAR H. (Biological Sciences - PJSIR, 2022)
A study on 50 soils with wide range of properties was conducted to find out a simple, rapid and reliable method of obtaining an index or soil N availability. Three chemical methods; mineral plus mincralizablc N determination by modified alkaline permanganate method, mineral N as (NH4 + NO)) and NOJ-N estimation by 2 NKCI were found promising as the soil N values obtained by these methods showed high correlation with mineral N of incubation test (r = 0.92, 0.88 and 0.85, respectively) and N uptake by wheat plants (r = 0.90, 0.87 and 0.85, respectively). The relationship between yield response of wheat plants to applied N in pots and soil available N determined by the three methods was also studied.